Part II: Minimum Quality Threshold in Preclinical Sepsis Studies (MQTiPSS) for Types of Infections and Organ Dysfunction Endpoints. Issue 1 (January 2019) - Libert, Claude; Ayala, Alfred; Bauer, Michael; Cavaillon, Jean-Marc; Deutschman, Clifford; Frostell, Claes; Knapp, Sylvia; Kozlov, Andrey V.; Wang, Ping; Osuchowski, Marcin F.; Remick, Daniel G.
Abstract : ABSTRACT: Although the clinical definitions of sepsis and recommended treatments are regularly updated, a systematic review has not been done for preclinical models. To address this deficit, a Wiggers-Bernard Conference on preclinical sepsis modeling reviewed the 260 most highly cited papers between 2003 and 2012 using sepsis models to create a series of recommendations. This Part II report provides recommendations for the types of infections and documentation of organ injury in preclinical sepsis models. Concerning the types of infections, the review showed that the cecal ligation and puncture model was used for 44% of the studies while 40% injected endotoxin. Recommendation #8 (numbered sequentially from Part I): endotoxin injection should not be considered as a model of sepsis; live bacteria or fungal strains derived from clinical isolates are more appropriate. Recommendation #9: microorganisms should replicate those typically found in human sepsis. Sepsis-3 states that sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection, but the review of the papers showed limited attempts to document organ dysfunction. Recommendation #10: organ dysfunction definitions should be used in preclinical models. Recommendation #11: not all activities in an organ/system need to be abnormal to verify organ dysfunction. Recommendation #12: organ dysfunction should be measured in an objective manner using reproducible scoring systems. Recommendation #13: not all experiments must measure all parameters of organ dysfunction, but investigators should attempt to fully capture as much information as possible. These recommendations are proposed as "best practices" for animal models of sepsis.